Application of a partial cell recycling chemostat for continuous production of aroma compounds at near-zero growth rates - van Mastrigt, Oscar (BMC Res Notes, 2019)
OBJECTIVE: The partial cell recycling chemostat is a modification of the chemostat in which cells are partially recycled towards the bioreactor. This allows using dilution rates higher than the maximum growth rate resulting in higher biomass concentrations and increased process rates. In this study, we demonstrate with a single observation that this system can also be used to study microorganisms at near-zero growth rates and as production system for compounds specific for slow growth, such as those typical for ripened cheese. RESULTS: Lactococcus lactis FM03-V2 was cultivated at growth rates between 0.0025 and 0.025 h(−1). Detailed analysis of produced aroma compounds revealed that levels of particular compounds were clearly affected by the growth rate within the studied range demonstrating that we can steer the aroma production by controlling the growth rate. With this approach, we also experimentally validated that the maintenance coefficient of this dairy strain decreased at near-zero growth rates (6.4-fold). An exponentially decreasing maintenance coefficient was included in the growth model, enabling accurate prediction of biomass accumulation in the partial cell recycling chemostat. This study demonstrates the potential of partial cell recycling chemostat both as aroma production system at near-zero growth rates and as unique research tool. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4213-4) contains supplementary material, which is available to authorized users.